Pengaruh Literasi Keuangan dan Kontrol Diri terhadap Perilaku Pengelolaan Keuangan pada Generasi Z (Studi Kasus pada Generasi Z di Kabupaten Karawang) - Soliha, Imaniar Amalia; Sihabudin; Lukita, Carolyn (Syntax Literate, 2023)
This research was carried out with the aim of investigating the influence of financial literacy and self-control abilities on the financial management behavior of generation Z in Karawang Regency. The research method applied was a quantitative approach involving 100 respondents who were generation Z in the area. To analyze the data, this research uses SPSS statistical software. The results of the research reveal that partial financial literacy has a significant impact on the way generation Z in Karawang Regency manages their finances. Then, the self-control ability variable also turns out to have a strong influence on their financial management behavior. Furthermore, overall, these findings confirm that financial literacy and self-control abilities, when combined, have a significant impact on the financial management behavior of generation Z in Karawang Regency. It is hoped that this research will provide valuable insight into the importance of financial literacy and self-control in optimizing financial management for generation Z.